Effects of greenhouse gas emissions timing on alternative biomass and fossil energy sources for district heating. Issue 11 (1st September 2021) - Kar, Saurajyoti; Billen, Pieter; Björnebo, Lars; Katz, Beth; Yang, Sheng; Volk, Timothy A.; Spatari, Sabrina
Abstract: District heating (DH) systems can improve energy efficiency, reduce greenhouse gas (GHG) emissions, and be a cost‐effective residential space heating alternative over conventional decentralized heating. This study uses radiative forcing (RF), a time‐sensitive life cycle assessment metric, to evaluate space heating alternatives. We compare forest residue and willow biomass resources and natural gas as fuel sources against decentralized heating using heating oil. The comparison is performed for selected locations in the Northeastern United States over a 30‐year production timeline and 100 observation years. The natural gas and willow scenarios are compared with scenarios where available forest residue is unused and adds a penalty of GHG emissions due to microbial decay. When forest residues are available, their use is recommended before considering willow production. Investment in bioenergy‐based DH with carbon capture and storage and natural‐gas‐based DH with carbon capture and storage (CCS) technology is considered to assess their influence on RF. Its implementation further improves the net carbon mitigation potential of DH despite the carbon and energy cost of CCS infrastructure. Soil carbon sequestration from willow production reduces RF overall, specifically when grown on land converted from cropland to pasture, hay, and grassland. The study places initial GHG emissions spikes from infrastructure and land‐use change into a temporal framework and shows a payback within the first 5 years of operation for DH with forest residues and willow. Abstract : Replacing conventional heating oil‐based decentralized residential heating with natural gas, forest residue, or willow feedstocks, and centralized‐district heating (DH) infrastructure significantly improves environmental performance. The study implements a temporal analysis using radiative forcing for 30 production years and 100 observation years, identifying the inflection points of greenhouse gas (GHG) emissions for the various residential heating feedstocks. Consideration of carbon capture and storage (CCS) and bioenergy CCS for natural gas and biomass‐based DH respectively shows significant atmospheric carbon capture. Such carbon capture technology supplements soil carbon sequestration‐based environmental GHG sequestration, for willow when grown on pasture, hay, and grasslands.